Cost Efficiency Analysis on Revenue Based on Budget Plan and Benefit-Cost Ratio in Oil Palm Plantation at Pabatu Estate PTPN IV Regional II North Sumatra Province - Alfisyahrin Farizi; Saprida; Desy Rahmawati Hasibuan (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
This study discusses the analysis of cost efficiency in relation to revenue in the oil palm cultivation business at PTPN IV Pabatu Plantation, located in Tebing Tinggi District, Serdang Bedagai Regency, North Sumatra Province. The analysis was conducted for the period from January to December in the years 2021, 2022, and 2023. The study uses secondary data in the form of the Budget Plan (RAB) and actual cost realization and applies the Benefit Cost Ratio (BCR) method as a tool to evaluate operational efficiency. This method is used to assess whether the operational expenses incurred are proportional to the revenue generated. The research was conducted in December 2024. The results show a BCR value of 3.21 in 2021, 2.86 in 2022, and 2.22 in 2023. Although the BCR values show a declining trend over the three-year period, all values remain above 1, indicating that the plantation operations are still efficient. Therefore, it can be concluded that cost management at PTPN IV Pabatu Plantation during this period continued to produce positive outcomes in terms of revenue.